VIRTUAL LEARNING DESIGN OF PROSE APPRECIATION COURSE WITH TEAM BASED PROJECT MODEL - Nurmalawati; Sitti Aminah; Arista Ardilla (RADJA PUBLIKA, 2024)
The world of education continues to develop, including in the lecture system which is now increasingly adopting online learning methods. One of the affected courses is Prose Appreciation, where based on evaluations in several in Lhokseumawe City, the level of student understanding of the material only reaches 45-85%. To increase the effectiveness of learning, a team-based project model is applied which allows students to be more active, creative, and produce products in the learning process. This study aims to analyze needs, formulate development principles, and design team-based project-based virtual lectures in Prose Appreciation courses. The method used in this research is research and development, which includes the stages of research and data collection, research planning, design draft development, design validation, and design revision. The learning model developed is based on eight main principles, namely motivation, pleasant learning atmosphere, modeling, guidance, guidance, direct experience, habituation, and exemplary. The model design consists of several main components, including introduction, objectives and assumptions, syntagmatics, social systems, reaction systems, support systems, and instructional and accompanying impacts. The implementation of the model is carried out by developing team- based project-based learning tools for online Prose Appreciation courses in Lhokseumawe City.